ChemInform Abstract: 9H‐Carbazole Derivatives Containing the N‐Benzyl‐1, 2, 3‐triazole Moiety as New Acetylcholinesterase Inhibitors. Issue 37 (September 2015) - Akrami, Hamidreza; Mirjalili, Bibi F.; Khoobi, Mehdi; Moradi, Alireza; Nadri, Hamid; Emami, Saeed; Foroumadi, Alireza; Vosooghi, Mohsen; Shafiee, Abbas
Abstract A series of triazole‐containing carbazole derivatives (III) is simply formed via a one‐pot three‐component click reaction.